Administrators’ Power Usage Styles and Their Impact on the Organizational Culture in Colleges of Education: A Case Study - Özcan, Kenan; Karataş, İbrahim Hakan; Çağlar, Çağlar; Polat, Murat (My University, 2014)
The main purpose of this study is to determine how power usage styles of administrators of faculties of education influence the organizational culture in their respective faculties in Turkey. Using the phenomenological method, a qualitative research method, researchers studied a group comprised of 20 academics from 7 different colleges of education employed during the 2011-2012 academic year. In order to select the appropriate study group, maximum variation technique was used since it is one of the purposive sampling methods. The data were gathered using semi- structured interview questions developed by the researchers themselves and were analyzed using descriptive statistical techniques. In this study, it was found that while the administrators of this group mostly used legal, coercive, and reward power styles, charismatic and expertise power styles did not have a significant impact on members of their respective faculties. It was further found that administrators’ usage of legal, coercive, and reward power styles bread both organizational cultures of power and bureaucracy. It was concluded that, due to the lack of charismatic and expertise power styles, cultures of success and support are unable to flourish in such faculties and that there are even difficulties in setting up a fully functional bureaucratic culture. As a result of this study, the researchers have suggested that in order to develop an organizational culture with all of its necessary components in faculties of education, administrators should be assigned through democratic selection methods, that they be trained in administrators training programs, and that a peer mentoring system should be developed in faculties of education.
Keywords: Eğitim, Eğitim Araştırmaları